STUDENT DIFFICULTIES IN ENGLISH PROUNCIATION - Husni, Rauldatul; Islamiah, Islamiah (Jurnal Ilmiah Wahana Pendidikan, 2023)
Student Difficulties In English Prounciation.This research uses a literature study with a qualitative approach. The data collection technique is to find various sources of theories from past research by collecting, analyzing, organizing sources from the articles obtained related to the discussion in this research. This research discuss about Student Difficulties In English Prounciation especially for student who are not fro english department in an institution s.